Republic of Pakistan Study in political geography (Journal of the College of Basic Education, 2023)
The state is the central element in the study of political geography because it has become the poleAttractive to all human activities, but their influence exceeds the role of natural factors. I got involvedhuman life and activities in a way that he cannot escape from. The state relies on its strength and influenceFor other countries, the availability of a set of elements, some of which are related to land resources.within the areas and extensions it occupies. and others, which are the most importantin the cultural, social and economic level of the population and their constant work within thisLimits to exploit these resources and increase production and wealth. Hence the power of the state is represented in itthe outcome of these social factors.